Conjugate impedance matched metamaterials: physical modeling and wave interaction effects - Maslovski, Stanislav I. (2018)
Conjugate impedance matched metamaterials are shown to be effective traps for electromagnetic waves. Objects made of such materials are able to receive radiation even when it is not directly incident on their surface. Here, we develop methods of physical modeling of such objects and investigate interactions of conjugate impedance matched superabsorbers with passing electromagnetic radiation. We study realizations of such metamaterials with meshes of loaded transmission lines and develop a theory of electromagnetic wave propagation and absorption in such media. Peculiar wave propagation, wave trapping and absorption effects in metamaterial black holes and wormholes are demonstrated. Possible modifications under the goal of optimizing absorption while minimizing complexity of the involved metamaterials are discussed. Conjugate-impedance matched superabsorbers may find applications as efficient harvesters of electromagnetic radiation, and as novel antennas and sensors.